Readings of Foucault in the regulation of the school community (Práxis Educativa, 2011)
This paper questions some readings, which are recurrent in the educational field, of works by the French philosopher Michel Foucault referring to processes of discipline and control in the school spaces-times of contemporaneity. Based on records of an ethnographic case study conducted in a public school of the municipal education system of Rio de Janeiro, questions are put to the freedom vs. oppression dichotomy with which school relationships are frequently interpreted, based on the aforementioned readings. In conclusion, emphasis is put on the up-to-dateness of the antiauthoritarian critique found in Foucault’s propositions under discussion, noting that such critique is not jeopardized by the questioning of its appropriations in binary simplification. Keywords: Discipline. Control. Foucault.